THE INFLUENCES OF PEERS TOWARDS SAYURI’S ADOLESCENCE IN MEMOIRS OF A GEISHA BY ARTHUR GOLDEN - Bule, Sitti F; Liru, Marianus W; Kara, Yuliana M D K (Lantern: Journal of Language and Literature, 2022)
The current study was intended to find out Sayuri’s adolescence development in Arthur Golden Memoirs of a Geisha and the influences of peers towards Sayuri’s adolescence in Arthur Golden Memoirs of a Geisha. This study used descriptive qualitative method. In analysing the data, some steps were adopted by by classifying and explaining the data based on the theories, and paraphrasing and analysing the quotations related to the problems. Based on the data analysis, there are three aspects of getting her personality, namely searching for identity; the adolescence rebellion; adolescent sexuality. The influence of peers based on two aspects, namely the relationship between peers and the interaction between peers. In their relationship, peers influence how to talk, dress, and be as a perfect woman. In their interaction, the influences occurred to build up the attitude and personality.